Peningkatan Kreativitas Pembelajaran Ipa Melalui Strategi Example Non Example Dengan Media Puzzle Pada Siswa Kelas IV Sd Muhammadiyah 11 Mangkuyudan Tahun 2015/2016 - Puspitasri, Riya Dwi, Dr. Achmad Fathoni, S.E., M.Pd (2016)
This research aims to determine the increase of learning creativity of science using the learning strategies example non example with puzzle media on fourth grade Muhammadiyah 11 Mangkuyudan Surakarta. This research is a classroom action research. The subject of this research are fourth grade students Muhammadiyah 11 Mangkuyudan Surakarta. The collecting of data through observation, interviews, documentation, and testing. The result showed an increase in learning creativity of science as follows: at pre cycle have a curiously level of 21% or 8 students, have a strong imagination level of 44% or 17 students, have and appreciate beauty of 42% or 16 students, and can work independently 38% or 15 students. At the first cycle have a curiously level of 51% or 20 students, have a strong imagination level of 72% or 28 students, have and appreciate beauty of 59% or 23 students, and can work independently 56% or 22 students. While at second cycle have a curiously level of 82% or 32 students, have a strong imagination level of 95% or 37 students, have and appreciate beauty of 92% or 36 students, and can work independently 87% or 34 students. From the research can be summed up through the application of learning strategies example non example with puzzle media can improve student learning creativity of fourth grade Mangkuyudan Surakarta muhammadiyah 11 2015/2016.